Analysis Of Factors Affecting Stunting Incidence In Indonesia : Literatur Riview - Nailuvar, Regita; Hilmi, Indah Laily; Salman, Salman (Jurnal EduHealth, 2022)
This study aims to analyze the factors that influence the occurrence of stunting Stunting is a problem in child development. Factors causing stunting were based on the most influencing factors, namely: family income, exclusive breastfeeding, the work of the toddler's father, the nutritional knowledge of the toddler's mother, and the baby's birth weight. This research method is a kind of literature survey study from various international and national journals, which tries to summarize the current understanding of the topic. Stunting inhibits children's optimal growth and development and can make them more susceptible to infection. Many factors can influence the occurrence of stunting in early childhood, including maternal factors, small child factors, and environmental factors. Based on the results of the analysis, the prevalence of stunting in children under 5 years (toddlers) in Indonesia in 2015 was 36.4%. This means that more than a third of children under the age of five or about 8.8 million experience nutritional problems if their height is below normal.